The Development of a Collaborative Binational Strategy to Support the San Diego-Tijuana Transborder Community During the COVID-19 Pandemic - Jiménez, Barbara; Kozo, Justine (Frontiers in Public Health, 2022)
At the start of the COVID-19 pandemic, it was evident that the challenges facing San Diego, California were the same ones facing Tijuana, Baja California; both experienced a rapid increase in cases, outbreaks, hospitalizations, and mortality. This was expected as San Diego and Tijuana are an interconnected region, home to one of the busiest international borders in the world, with hundreds of thousands bi-directional crossings in a single day. With the rising case numbers, it was essential and urgent to implement a formal structure to facilitate cross-border COVID-19 communication, coordination, and collaboration. The proposed article will describe how the development of a Collaborative Binational Strategy led to coordinated outreach and initiatives that addressed access and equity in the transborder region. The article will provide examples of how regional leaders in San Diego and Tijuana harnessed existing transborder partnerships to collaboratively build infrastructure and communication pathways to exchange data, guidance, troubleshoot shared challenges, build capacity, and establish cross-border testing and vaccine opportunities. Through case studies, the article will present challenges, lessons learned, and best practices that can inform other multi-level, interdisciplinary, and cross-border jurisdictions on how to support a transborder community during a pandemic or other health emergency.